Eksistensi Pendidikan Islam Nu dan Muhammadiyah sebagai Potret Islam Moderat di Indonesia - Yumnah, Siti (Proceedings of Annual Conference for Muslim Scholars, 2022)
As "Islam with a cheerful face", Indonesian Islam is known as a peaceful and moderate Islam, so there is no conflict with modernity, democracy, human rights, or other tendencies in the modern world. The importance of government groups and non-governmental organizations to sow and strengthen moderate Islam through education, whether formal, informal, or non-formal. Muhammadiyah and NU, which were labeled as moderate Islam from the start, are likely to play an important role in empowering moderate Islam in Indonesia. It is time for moderate religious mass organizations, such as NU and Muhammadiyah, to direct religious groups to channel their religious militancy through wisdom, not terror and bloodshed. This paper aims to see how effective the existence of NU and Muhammadiyah Islamic Education is in promoting moderate Islam in Indonesia.